Apocalypticism as Radical Realism? On the Dangers and Benefits of Wishful Thinking in Prefigurative Politics. (May 2023) - Cross, Ben
In this article, I aim to bring apocalypticism and radical realism into conversation, with a view to their mutual interest in prefigurative politics. On one hand, radical realists may worry that an apocalyptic approach to prefigurative politics may be marred by wishful thinking. On the other hand, radical realists can (and sometimes do) acknowledge that wishful thinking is sometimes desirable. I argue that an apocalyptic approach to prefigurative politics suggests one way of guarding against the dangers of wishful thinking, while allowing space for its potential benefits; prefigurativists have reason to pay at least some attention to what Bernard Williams calls 'The First Political Question'. I will argue for this claim with reference to the case of Omar Aziz, a Syrian activist who played a pivotal role in the construction of local councils in the aftermath of the 2011 protests.